Impacts of future urbanization on urban microclimate and thermal comfort over the Mumbai metropolitan region, India. (April 2022) - Vinayak, Bhanage; Lee, Han Soo; Gedam, Shirishkumar; Latha, R.
Highlights: Microclimatic effects of future urbanization on MMR were assessed by WRF-UCM model. The temperature of suburban centers is likely to increase along with urbanization. Future urbanization pattern will have negligible impact on wind speed. By 2050, discomfort hours over newly urbanized area will increase by 3–5 h/day. The cool roof/wall-based mitigation plan is able to curb the future temperature increase. Abstract: This study examines the microclimatic impacts of future urbanization over the Mumbai Metropolitan Region (MMR) in India using a dynamic downscaling approach. Initially, two numerical experiments (curr_exp and fut_exp) were carried out by integrating 2018 and 2050 land-use/land-cover patterns under the same meteorological conditions. Afterwards, the spatial and temporal changes in surface air temperature, wind speed, and thermal discomfort were assessed by comparing the simulated results between curr_exp and fut_exp. To remediate the observed adverse microclimatic impacts of future urbanization, a mitigation strategy was designed and implemented in the third experiment (miti_exp). Simulation results show that the average maximum (minimum) surface air temperature of the region would increase by 1.41 °C (1.27 °C) due to future urbanization. However, if we adopt the mitigation strategy, this growth can be restricted to 0.69 °C (0.92 °C). In the context of thermal discomfort, an additional 20% of the total area can undergo hyperthermal treatment by 2050. This study reveals that although the implemented mitigation strategy can restrict the increasing temperature, it is ineffectual in minimizing the thermal discomfort level. The results of this study will be helpful in designing area-specific climate action plans through which goals of sustainable urban development can be accomplished.